LEGALINFORMATICS AND SECURITY OF INFORMATION SYSTEMS IN CIVIL AVIATION - Цимбалюк, В. С. (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2008)
The article deals with the legal issues of the organization of computer science and security of information systems in aviation.